The relationship between Th1/Th2 cytokine polarization and milk composition in the postnatal period in Kyrgyz mares and foals - Istanbullugil, Fatih R.; Risvanli, Ali; Salikov, Ruslan; Bayraktar, Metin; Kadiraliyeva, Nariste; Zhunushova, Aidai; Asinbekovic, Mirbek I. (Wiley, 2023)
Immune compatibility between mare and foal is one of the important topics of reproductive immunology. At this point, although there are many studies on antibodies, there are not many publications on the relationship between the cytokine levels of mare, foal and milk and the effects of milk composition on this relationship. Here we investigate the relationship between Th1/Th2 cytokine balance and milk composition in Kyrgyz mares and foals. Samples were taken soon after the foal was born and on days 5, 10 and 20 after birth. Th1 (IFN-gamma, IL-2, TNF-alpha) and Th2 (IL-4, IL-5, IL-10) cytokine levels in blood samples were measured using a commercial ELISA kit. Dry matter, fat, protein and non-fat dry matter ratios were determined in the mare's milk and colostrum. We detected no Th1/Th2 polarization in the mare's milk on the day of the foal's birth (day 0) and day 10, but there was Th1 polarization on day 5 and Th2 cytokine polarization on day 20. There was no polarization in the blood sera of the mares on days 0, 5, and 10, and Th1 cytokine polarization was also detected on day 20. We detected no Th1/Th2 cytokine polarization in the blood sera of the foals on any of the days. Dry matter (19.66 +/- 0.39%), protein (16.56 +/- 0.18%), fat (2.13 +/- 0.17), and non-fat dry matter (17.59 +/- 0.44%) were higher in colostrum than the other days. When the correlations between cytokine levels in milk samples and milk composition were examined, there was a positive correlation between IL-5 level and protein ratio on day 10. We detected a positive correlation between IL-2 level and the fat rate on day 20. There was a positive correlation between the IL-2 level and the non-fat dry matter ratio on day 20. Further studies are now needed to determine the relationship between the changes in the composition of mare's milk in the postnatal period and Th1/Th2 cytokine polarization in mares and foals at the time of birth and in the postnatal period. Our finding that protein and fat ratios in mare's milk in the postnatal period are positively correlated with IL-2 levels should be considered in terms of foal and human nutrition.
Keywords: cytokine; foal; Kyrgyz mares; mare milk